Dementia with lewy bodies patients with high tau levels display unique proteome profiles - Sinead Greally; Mukesh Kumar; Christoph Schlaffner; Hanne van der Heijden; Elisabeth S. Lawton; Deeptarup Biswas; Sabina Berretta; Hanno Steen; Judith A. Steen (Molecular Neurodegeneration)
Abstract Background Clinical studies have long observed that neurodegenerative disorders display a range of symptoms and pathological features and, in some cases, overlap, suggesting that these diseases exist on a spectrum. Dementia with Lewy Bodies (DLB), a synucleinopathy, is a prominent example, where symptomatic similarities with tauopathy, Alzheimer’s disease, are observed. Although tau pathology has been observed in DLB, the interplay between tau and α-synuclein is poorly understood at a molecular level. Methods Quantitative mass spectrometry analysis was used to measure protein abundance in the insoluble fraction from cortical brain tissue from pathologically diagnosed DLB subjects (n = 30) and age-matched controls (n = 29). Using tau abundance, we stratified the DLB subjects into two subgroups termed DLBTau+ (higher abundance) and DLBTau− (lower abundance). We conducted proteomic analysis to characterize and compare the cortical proteome of DLB subjects exhibiting elevated tau, as well as the molecular modifications of tau and α-synuclein to explore the dynamic between tau and α-synuclein pathology in these patients. Results Proteomic analyses revealed distinct global protein dysregulations in DLBTau+ and DLBTau− subjects when compared to controls. Notably, DLBTau+ patients exhibited increased levels of tau, along with ubiquitin, and APOE, indicative of cortical proteome alterations associated with elevated tau. Comparing DLBTau+ and DLBTau− groups, we observed significant upregulation of cytokine signaling and metabolic pathways in DLBTau− patients, while DLBTau+ subjects showed increases in protein ubiquitination processes and regulation of vesicle-mediated transport. Additionally, we examined the post-translational modification patterns of tau and α-synuclein. Our analysis revealed distinct phosphorylation and ubiquitination sites on α-synuclein between groups. Moreover, we observed increased modifications on tau specifically within the DLBTau+ subgroup. Conclusion This molecular-level data supports the idea of neurodegenerative disease as a continuum of diseases with distinct PTM profiles DLBTau+ and DLBTau− patients in comparison to AD. These findings further emphasize the importance of identifying specific and tailored therapeutic approaches targeting the involved proteopathies in the neurodegenerative disease spectrum.